Studi Deskripsi Subjective Well-Being Korban Poliviktimisasi Perundungan di Kota Bandung - Labibah Nur Hasanah; Borualogo, Ihsana Sabriani (Bandung Conference Series: Psychology Science, 2024)
Abstract. Bullying has a negative impact on the subjective well-being (SWB) of children and adolescents. In Indonesia, there is a lot of research discussing bullying and its relationship with the SWB of children, but research on polyvictimization of bullying is still limited. Polyvictimization of bullying is a condition where students experience more than one form of bullying incident conducted by different perpetrators in different settings. This study aims to provide a description of cases of polyvictimization of bullying in schools by other student in school and also at home conducted by siblings experienced by junior high school students in the city of Bandung, and how their SWB is described. Participants in this study were junior high school students in Bandung in grades 7, 8, and 9 (N = 160) with a gender ratio of 56.3% female and 43.8% male. The sampling technique used was cluster random sampling. The measurement tools used included the frequency of bullying from Children's Worlds (α = 0.895), socio-economic status (SES), CW-PNAS (α = 0.975), and CW-SWBS5 (α = 0.525). The results of the study showed that the average SWB scores of male students who were victims of polyvictimization of bullying (M = 79.0; SD = 22.1) were higher than the SWB scores of female students (M = 59.7; SD = 30.2). Female students also showed a more dominant negative affect (M = 67; SD = 30.5) compared to male students (M = 53; SD = 31.8). Overall, junior high school students who were victims of polyvictimization of bullying in Bandung had SWB scores (M = 68.1; SD = 27.4), which means that these students did not feel a sense of well-being. Abstrak. Perundungan memberikan dampak yang negatif teerhadap subjective well-being (SWB) anak dan remaja. Di Indonesia banyak penelitian yang membahas mengenai perundungan dan hubungannya dengan SWB anak, namun penelitian yang membahas mengenai poliviktimisasi perundungan masih terbatas. Poliviktimisasi perundungan adalah kondisi di mana siswa mengalami lebih dari satu perundungan yang dilakukan oleh pelaku yang berbeda dan dilakukan pada setting tempat yang berbeda. Penelitian ini bertujuan untuk memberikan deskripsi kasus poliviktimisasi perundungan di sekolah dan di rumah oleh siswa lain di sekolah dan juga saudara kandung yang dialami oleh siswa SMP di Kota Bandung dan bagaimana deskripsi SWB mereka. Partisipan pada penelitian ini adalah siswa SMP di Kota Bandung yang berada di kelas 7, 8 dan 9 SMP (N = 160) dengan perbandingan jenis kelamin sebanyak 56.3% perempuan, 43.8% laki-laki. Teknik sampling yang digunakan adalah cluster random sampling. Alat ukur yang digunakan adalah frekuensi perundungan dari Children’s Worlds (α=.895), socio economic status (SES), CW-PNAS (α=.975) dan CW-SWBS5 (α=.525). Hasil penelitian menunjukkan bahwa rata-rata skor SWB siswa laki-laki korban poliviktimisasi perundungan (M = 79. ; SD = 22.1) lebih tinggi dibandingkan dengan skor SWB siswa perempuan (M = 59.7; SD = 30.2). Siswa perempuan juga menunjukkan lebih dominan negative affect (M = 67; SD = 30.5) dibandingkan dengan siswa laki-laki (M = 53; SD = 31.8). Secara keseluruhan siswa SMP yang menjadi korban poliviktimisasi perundungan di Kota Bandung memiliki skor SWB (M = 68.1; SD = 27.4), yang berarti siswa SMP korban poliviktimisasi perundungan di Kota Bandung tidak merasa well-being.